Working Remotely During the COVID-19 Pandemic: Efforts of the Ministry of Education in the United Arab Emirates - Rawdha AlMarar; Amani Alkhodari; Dina Y. Atia; Satti Mohamed; Raed M Shubair (TIJAB (The International Journal of Applied Business), 2021)
Following the global outbreak of COVID-19 pandemic, work is no longer being conducted in the traditional manner. This has created pressure on businesses to shift into a mode of remote working in order to avoid severe disruption. The United Arab Emirates (UAE) has attempted to face challenges accompanying this crisis and explore solutions with the wise vision and constant support of its leadership. This paper examines the transition of working procedures at one of the most influential entities in the UAE; the Ministry of Education (MOE). The purpose here is to shed light on how obstacles have been turned into opportunities in order for MOE employees to continue working remotely during such critical conditions. This is illustrated by the efforts of ministry departments that were interviewed for their feedback during the study. This paper provides insights into the activation of remote work in response to sudden incidents by highlighting measurements and factors that contribute to entities’ readiness for such a transition. This study analyzes the value and originality of MOE remote working practices and their impact on the wider community.